Deep Trade Agreements and Firm Ownership in GVCs - Egger, Peter H. (The World Bank, 2023)
This paper focuses on the effect of preferential trade agreements and their depth on firm ownership, in particular, along global value chains. It measures shareholder-affiliate ownership links at the country-sector-pair level to discern between vertical and horizontal links. The findings show that preferential trade agreements boost vertical international investment links (both backward and forward) while reducing horizontal investment. Deep preferential trade agreements stimulate investment particularly for sector pairs, where a high input specificity prevails
Keywords: Foreign Direct Investment; Foreign Ownership; International Economics and Trade; International Investment; Preferential Trade Agreement (PTA); PTA Depth